From Egypt to Ireland: Lady Augusta Gregory and Cross-Cultural Nationalisms in Victorian Ireland - Bobotis, Andrea (Romanticism and Victorianism on the Net, 2007)
Abstract“From Egypt to Ireland: Lady Augusta Gregory and Cross-Cultural Nationalisms in Victorian Ireland” argues that Gregory promoted women’s political activism by adapting and exploiting the ways that nineteenth-century Irish nationalists drew upon African and Asian cultures to forge new understandings of Irishness. Gregory turned to representations of an Egyptian nationalist and his family to advocate links between domestic space and political action, a proposition that underscored Gregory’s elite class position, but also revealed the potential of the essay form to revise assumptions about gender that had calcified in other prevalent genres of Victorian Ireland.